REALASI ILMU PENGETAHUAN DAN AGAMA - Hidayatulloh Hidayatulloh (Proceedings of The ICECRS, 2016)
The relation of science and religion found several models that are dichotomous relationship, dialogue, parallel, harmonious, even conflict or integration. It all depends on the attitude and depth of a paradigm used. M. Amin Abdullah stated that there are three approaches that bore pattern model of the relationship between science and religion, namely: (1) models of single entity, religious knowledge stand alone without the need for another science methodology, and vice versa; (2) model of isolated entities, each clump of science stands alone, not bersetuhan, not admonished methodologically courtesies; and (3) model of interconnected entities, each aware of the limitations in solving problems, and both are cooperating in terms of approaches, methods of thought and research.The relation of science and religion form model of integration and interconnection of science. The model may be developed is a model of integration-dialectical interconnections. This model is understood as a model of integration that tries to dialect between science and religion. The dialectical integration can manifest in the form of: (1) integration into the design of learning and / or programs of study; and (2) Integration in the attitude of scientists.